2021
DOI: 10.3389/fped.2021.678890
|View full text |Cite
|
Sign up to set email alerts
|

Management and Clinical Outcome of Posterior Reversible Encephalopathy Syndrome in Pediatric Oncologic/Hematologic Diseases: A PRES Subgroup Analysis With a Large Sample Size

Abstract: This study investigated the management and clinical outcomes along with associated factors of posterior reversible encephalopathy syndrome (PRES) in childhood hematologic/oncologic diseases. We present data from children with hematologic/oncologic diseases who developed PRES after treatment of the primary disease with chemotherapy and hematopoietic stem cell transplantation (HSCT) at 3 medical centers in Changsha, China from 2015 to 2020, and review all previously reported cases with the aim of determining whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 113 publications
0
4
0
Order By: Relevance
“…found that mortality among PRES with HSCT was two times that of oncologic or hematologic disease where 65% of patients were receiving chemotherapy of which 44.8% were in induction regimen and 86.5% were on corticosteroids before the onset of PRES. [ 6 ]…”
Section: Discussionmentioning
confidence: 99%
“…found that mortality among PRES with HSCT was two times that of oncologic or hematologic disease where 65% of patients were receiving chemotherapy of which 44.8% were in induction regimen and 86.5% were on corticosteroids before the onset of PRES. [ 6 ]…”
Section: Discussionmentioning
confidence: 99%
“…Although it may develop in patients with many medical conditions (typically renal failure and hypertension), PRES can occur in children undergoing cancer treatment, most commonly in those with hematologic malignancies, and who have undergone allogeneic hematopoietic cell transplant. [8][9][10][11][12] Medications that have been associated with PRES include vincristine, cisplatin, methotrexate (MTX), L-asparaginase, and immunosuppressive agents. 13 Clinical symptoms may include seizures, altered mental status, and/or headache.…”
Section: Short-term Complications Posterior Reversible Encephalopathy...mentioning
confidence: 99%
“…15 Treatment involves supportive care, antihypertensives, antiepileptics, and interruption of offending agent, if possible. 8,11,12 Although most clinical and imaging findings are transient, abnormalities on magnetic resonance imaging (MRI) and seizures may persist in some (particularly in the presence of abnormal diffusion-weighted imaging changes), and death may occur in rare cases. 8,9,11,12…”
Section: Short-term Complications Posterior Reversible Encephalopathy...mentioning
confidence: 99%
See 1 more Smart Citation
“…Leukemia, particularly Acute Lymphoblastic Leukemia (ALL), a common pediatric cancer originating in the bone marrow, accounts for 20% of all childhood cancers. Despite treatment advancements, ALL remains a therapeutic challenge but boasts a promising prognosis, with a current 5-year overall survival rate of 90% [6] . It involves an excessive production of immature and abnormally differentiated leukocytes [7] .…”
Section: Introduction Overview Of Pediatric Blood Disordersmentioning
confidence: 99%